2000
DOI: 10.1046/j.1365-2958.2000.01849.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription activation at the Escherichia coli melAB promoter: the role of MelR and the cyclic AMP receptor protein

Abstract: SummaryMelR is a melibiose-triggered transcription activator that belongs to the AraC family of transcription factors. Using purified Escherichia coli RNA polymerase and a cloned DNA fragment carrying the entire melibiose operon intergenic region, we have demonstrated in vitro open complex formation and activation of transcription initiation at the melAB promoter. This activation is dependent on MelR and melibiose. These studies also show that the cyclic AMP receptor protein (CRP) interacts with the melAB prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 29 publications
1
79
0
Order By: Relevance
“…Taking our results together with previous data (Torres et al, 2003) we have demonstrated that the glucose effect on mhp expression is exerted at the level of both catabolic and regulatory promoters. This simultaneous CRP control is not unique to the mhp pathway, since it has been also described for the genes for propionate catabolism in E. coli and Salmonella enterica (Lee et al, 2005) and for some regulons from E. coli such as those for L-rhamnose (Holcroft & Egan, 2000;Wickstrum et al, 2005), melibiose (Webster et al, 1988;Belyaeva et al, 2000) and maltose (Chapon & Kolb, 1983;Richet & Sogaard-Andersen, 1994;Richet, 2000). While the expression of the mhpR, melR and malT regulators depends only on the presence of CRP (Webster et al, 1988;Chapon & Kolb, 1983), the expression of rhaSR and prpR depends on the presence of CRP and the transcription activators RhaR and PrpR, respectively (Tobin & Schleif, 1990a, b;Wickstrum et al, 2005;Lee et al, 2005).…”
mentioning
confidence: 76%
“…Taking our results together with previous data (Torres et al, 2003) we have demonstrated that the glucose effect on mhp expression is exerted at the level of both catabolic and regulatory promoters. This simultaneous CRP control is not unique to the mhp pathway, since it has been also described for the genes for propionate catabolism in E. coli and Salmonella enterica (Lee et al, 2005) and for some regulons from E. coli such as those for L-rhamnose (Holcroft & Egan, 2000;Wickstrum et al, 2005), melibiose (Webster et al, 1988;Belyaeva et al, 2000) and maltose (Chapon & Kolb, 1983;Richet & Sogaard-Andersen, 1994;Richet, 2000). While the expression of the mhpR, melR and malT regulators depends only on the presence of CRP (Webster et al, 1988;Chapon & Kolb, 1983), the expression of rhaSR and prpR depends on the presence of CRP and the transcription activators RhaR and PrpR, respectively (Tobin & Schleif, 1990a, b;Wickstrum et al, 2005;Lee et al, 2005).…”
mentioning
confidence: 76%
“…Recombinant plasmids were propagated in strain WAM131 (11), an mel ϩ strain derived from GM-1 (14). ␤-Galactosidase levels in these cells were measured using the method of Miller (15): cells * This work was supported by grants from the Ministry of Education, Science and Culture of Japan and from the United Kingdom Biotechnology and Biological Sciences Research Council.…”
Section: Methodsmentioning
confidence: 99%
“…1). First, using PCR, we amplified the KK81 fragment that carries the entire melAB promoter with all four MelR binding sites (sites 1Ј, 1, 2, and 2Ј) that are known to be essential for optimal melAB promoter activity (10,11). Second, we amplified the shorter JK14 fragment that carries the melAB transcript start site and only the MelR binding sites 2 and 2Ј.…”
Section: In Vivo Assays With the W3133-2 Mutant Melabmentioning
confidence: 99%
See 2 more Smart Citations